Perspectives of Filipino Youth on Poverty - Bernarte, Racidon (Social Sciences and Development Review, 2015)
The study sought a descriptive understanding of the perspective of Filipino youth on the issue of poverty in terms of the weight of the issue, causes of poverty, ways to reduce poverty and consideration if they are living in poverty. The study used a quantitative research approach to learn about the issue of poverty, its causes, and ways to reduce it from the perspective of Filipino youth. Primary data was collected through the use of self administered survey of 401 Filipino youth, comprised of college level students. Moreover, descriptive method was utilized in the research design of the study to give a quantitative description of the general perspective of the Filipino Youth on poverty. The Filipino Youth viewed poverty as a serious social issue and believed that this is caused by the top ten causes of poverty in the Philippines. Also, these causes are not independent of each other because several items in the ranking can be linked to one another just like corruption and poor governance, low-wage rates and poor quality of education, and poor welfare system and rapid population growth to name a few. Filipino Youth are well aware of the current events most especially what is happening in their government which are somehow related or resulted to other causes of poverty. With everyday challenges the youth faces from doing schoolwork and participating in recreational activities to making significant plans for the future, it is important to note that, even though most of the respondents came from the lower social classes or the proletariat class of the society, they do not consider themselves poor or living in poverty. The respondents strongly suggest that to reduce poverty there should be free quality education for all, more job opportunities and stop in corruption in government, among others.